New Platinum(II) Complexes Affecting Different Biomolecular Targets in Resistant Ovarian Carcinoma Cells. (6th April 2021) - Hyeraci, Mariafrancesca; Scalcon, Valeria; Folda, Alessandra; Labella, Luca; Marchetti, Fabio; Samaritani, Simona; Rigobello, Maria Pia; Dalla Via, Lisa
Abstract: Resistance to platinum‐based anticancer drugs represents an important limit for their clinical effectiveness and one of the most important field of investigation in the context of platinum compounds. From our previous studies, Pt II complexes containing the triphenylphosphino moiety have been emerging as promising agents, showing significant cytotoxicity to resistant ovarian carcinoma cells. Two brominated triphenylphosphino trans ‐platinum derivatives were prepared and evaluated on human tumor cell lines, sensitive and resistant to cisplatin. The new complexes exert a notable antiproliferative effect on resistant ovarian carcinoma cells, showing a remarkable intracellular accumulation and the ability to interact with different intracellular targets. The interaction with DNA, the collapse of mitochondrial transmembrane potential, and the impairment of intracellular redox state were demonstrated. Moreover, a selectivity towards the selenocysteine of thioredoxin reductase was observed. The mechanism of action is discussed with regard to the resistance phenomenon in ovarian carcinoma cells. Abstract : Increase targets, decrease resistance : Two new brominated trans‐ Pt II complexes show an interesting cytotoxicity on ovarian carcinoma resistant cells. Study of the mechanism of action reveals the ability to affect different biomolecular targets: interaction with DNA, inhibition of thioredoxin reductase and impairment of mitochondria were demonstrated.